Cost estimation of crop residue burning machine. Issue 1 (March 2021) - Sulastri, N N; Holcomb, R; Long, J; Buser, M
Abstract: The purpose of this study was to determine the cost of crop residue burning machine application based on several factors affecting its cost. Additionally, the cost was compared to the cost of prescribe burning practice. The total cost was determined by calculating fixed and variables costs. Those costs were computed mostly based on equations on ASAE EP496.2 DEC99 and ASAE D497.7 MAR2011(R2015). A Microsoft Windows®application was developed to systematically estimate the cost of the developed burning machine and to provide an additional tool for management decisions. Using the assumption of a-5 feet working width of the burning machine, the machine field efficiency of 60%, the travel speed of 1.9 mph, and a-20 acre of burn unit the total cost of burning practice using the developed burning machine was $164.78 which is comparable to prescribed burning cost on 134 acres of the burn unit. The important factor affecting the cost of the machine operation was the construction of firebreak and the acreage of machine use.